MALAYSIAN PADDY FARMERS AWARENESS AND PERCEPTION TOWARDS SYSTEM OF RICE INTENSIFICATION (SRI) PRACTICES: A PRELIMINARY STUDY - Nolila Mohd Nawi; Siti Samila Zainal (UPT Penerbitan Universitas Jember, 2012)
The increasing food demand coupled with declining water availability meant for food production cause further concerns towards food security due to increasing numbers of the world’s population. System of Rice Intensification (SRI) known as a relevant innovation and has emerge as an alternative to traditional way of flooded rice cultivation and is showing great promise to deal with the problems of water scarcity and low yield. Ithas been introduced to Malaysia in 2009 by Norman Uphoff a renowned SRI researcher. Since SRI just recently introduced to the country, thus the aims of this paper is to determine the farmers’ awareness and perception of SRI practices in their rice cultivation. A survey was conducted in February, 2012 in North-West Selangor district. Using a simple random sampling technique, 111 paddy farmers were selected and interviewed via a structured questionnaire. The results showed that most of the respondents (88%) are aware about the existence of SRI in their area. Further analysis using principal component analysis revealed two factors namely low cost of production and sustainable farming that collectively described farmer’s perception towards SRI practices. It shows that SRI covered both economic and environmental aspects of rice cultivation and it should be adopted by all paddy farmers in Malaysia to overcome the issues of food security and water crisis.